1998
DOI: 10.1002/(sici)1097-4628(19981107)70:6<1201::aid-app17>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of teflon AF1600 during XPS analysis

Abstract: Teflon AF1600, containing perfluorinated dioxole rings, was found to be particularly susceptible to X-ray degradation, such as that occurring during X-ray photoelectron spectroscopy. Because of the presence of O, the degradation mechanism is substantially different from those of fluoropolymers containing only C and F. Each atom of a given element was found to have the same susceptibility to attack, irrespective of its position in the repeat unit, with O at least twice as susceptible as F. At any dose between 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…More elaborate determinations of the surface structure are underway. Our XPS measurements are in agreement with Popovici et al , who demonstrated that irradiating Teflon AF with Mg Kα radiation at 1253.6 eV leads to the degradation of the polymer and formation of CO (Supporting Information SI2).…”
Section: Resultssupporting
confidence: 90%
“…More elaborate determinations of the surface structure are underway. Our XPS measurements are in agreement with Popovici et al , who demonstrated that irradiating Teflon AF with Mg Kα radiation at 1253.6 eV leads to the degradation of the polymer and formation of CO (Supporting Information SI2).…”
Section: Resultssupporting
confidence: 90%
“…While, as we have explained, the presence of several simultaneous phenomena (surface disorder, ligand field effects, and Russell−Saunders coupling) prevents our demonstration of surface disorder in the Fe 2p spectrum, this is not the case for the O 1s spectrum. There, we base ourselves on the fact that, since the inception of our laboratory in 1984 with its VG ESCALab 3 Mk II spectrometer, the width of the O 1s peak, in many different environments, has always been found to be 1.8 eV. ,,, We have thus found it possible to separate oxygen environments when several exist in a sample, whether organic or inorganic. It is for this reason that we undertook to explore the introduction of an additional O 1s peak in our oxide samples.…”
Section: Discussionmentioning
confidence: 99%
“…The C 1s spectrum of FC coated ITO in figure 3(a) can be resolved into five peaks located at 293.2 (CF 3 ), 291 (CF 2 ), 288 (COO), 286.5 (C-CF) and 284.5 (C-C or C-H) functional groups. The F1s spectral analysis shows the peak at 688.5 eV (F-C) by the fluoropolymer on the ITO surface, where the main peak can be further resolved with 3 component peaks due to CF 2 , CF 3 and CF in order of decreasing binding energies [17]. The atomic concentration of indium was decreased from 32.9% to 11.8% (530 eV peak in oxygen spectra, caused by indium oxide [18]).…”
Section: Resultsmentioning
confidence: 99%